CICERO'S ECLECTICISM AND ORIGINAUTY - van Zyl, D.H. (Akroterion, 1990)
One of the most strenuous debates in regard to Cicero turns upon the comroversial subject of hiseclecticism and originality, or lack of originality. Much of what is said on this subject, however,is simplistic or ill-considered, since it does not take account, on the one hand, of the relevantcircumstances pertaining to Cicero's eclecticism nor, on the other hand, of the basis upon whichhis originality should be adjudicated